2020
DOI: 10.18805/lr-4353
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Productivity and Profitability of Fodder Sorghum and Cluster Bean as Influenced by Mixed Cropping and Nutrient Management

Abstract: Background: The year round green forage supply for better health and productivity of the animals can be ensured by mixed cropping of cereal and legume forages along with proper nutrient management. Keeping these facts in mind an experiment was carried out to analyse growth, productivity and profitability of fodder sorghum and clusterbean as influenced by mixed cropping and nutrient management. Methods: Experiment was laid out in factorial randomized complete block design with four seed rate combinations of sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The enhanced level of organic matter under organic treatments also played an important role in raising soil physical health (Nandapure et al, 2011), as is evident from the correlation matrix (Table 7) and the heat map analysis (Figure 2), which indicates a strong relationship between soil properties. Another reason for the improvement of soil physical properties under FYM + MI could be due to maintained soilplant-water relationship in a better way as a result of proper root development and soil aggregation (Kumar et al, 2015;Graham et al, 2017;Singh et al, 2020b;Bhakar et al, 2021;. Accordingly, soils managed with organic manure, along with MI, tend to have more stable soil aggregates in comparison to inorganic fertilizers and MI combinations (Babu et al, 2015).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced level of organic matter under organic treatments also played an important role in raising soil physical health (Nandapure et al, 2011), as is evident from the correlation matrix (Table 7) and the heat map analysis (Figure 2), which indicates a strong relationship between soil properties. Another reason for the improvement of soil physical properties under FYM + MI could be due to maintained soilplant-water relationship in a better way as a result of proper root development and soil aggregation (Kumar et al, 2015;Graham et al, 2017;Singh et al, 2020b;Bhakar et al, 2021;. Accordingly, soils managed with organic manure, along with MI, tend to have more stable soil aggregates in comparison to inorganic fertilizers and MI combinations (Babu et al, 2015).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…The disruption of microbial diversity and, consequently, the bio-fertility, owing to the inappropriate nutrient management strategy, has become a concern for optimum soil health and plant growth (Fernández-Romero et al, 2016;Patra et al, 2016). In this context, the role of naturally abundant but functionally unexplored microorganisms, such as nitrogen fixing, phosphorus, and potash solubilizing microbial inoculants, along with their synergic integration with other organic sources of nutrients, such as bulky manures under a fertility augmentative legume crop, is crucial and offers a unique opportunity for balancing soil fertility, maintaining soil health, improving plant growth and profitable crop production in a sustainable way (Kumar et al, 2015;Gupta et al, 2020;Bhakar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated use of 20 kg N + 5 tonnes farmyard manure/ha in clusterbean + sesame intercropping system was most productive, remunerative and sustainable with better resource-use efficiency in arid region (Meena et al 2009). Growing of 75% sorghum+25% guar as mixed cropping with 75% RDF + seaweed extract produced nutritionally enriched fodder yield and profitable income (Bhakar et al 2020). The benefit-cost ratio calculated significantly higher under the nutrient-management practice of 50% RDN + 50% N-FYM + BF (2.07) over RDN (1.94) and control (1.77) but statistically at par with 50% RDN + 50% N-FYM (2.02).…”
Section: Resultsmentioning
confidence: 96%
“…It was concluded that growing of 75% sorghum + 25% guar mixed cropping with 75% RDF + seaweed extract produced most nutritionally enriched fodder in highest quantity and enriched the soil. Besides, this combination was economically profitable also (Bhakar et al 2020). Thus a portion of recommended dose of fertilizer could be substituted by organic sources of nutrients like PGPR and seaweed extract which had positive influence on root growth, yield and nutritional composition of both the fodder crops.…”
Section: Resultsmentioning
confidence: 99%